Pengaruh Teknik Assertive Training terhadap Rasa Percaya Diri Siswa - An-Nur Pasha Ramadhan; Taty Fauzi; Arizona Arizona (Kuras Institute, 2022)
The lack of self-confidence can hinder the development of students. The aim of this research is to find out whether assertive training techniques effect on students' self-confidence at MTs Negeri 1 Palembang. The method used in this research is a one group pretest posttest design. The population in this study was class VIII students at MTs N 1 Palembang with a sample of 10% of the total number of class VIII students, namely there were 30 samples. Data collection techniques in this study used a questionnaire and observation. This study focuses on the effect of assertive training on students' self-confidence. From the results of data analysis, the average pre-test 74.83 and the average post-test is 77.7. Tcount is -4.735 with a Ttable value of 2.045. The results obtained indicate an increase in the average value after the post-test. Thus, it can be concluded that the assertive training influences increasing the confidence of the students of MTs N 1 Palembang.